The Effect of Accountability and Transparency on the Management of Village Fund Allocation (Add) in Bonepantai District, Bonebolango Regency - Anggriani M. Usman; Radia Hafid; Fatmawaty Damiti (International Journal of Management Research and Economics, 2025)
Transparency is very influential on the allocation of village funds. The purpose of this study is to find out how much Accountability and Transparency Affect the Management of Village Fund Allocation (ADD) in Bonepantai District, Bonebolango Regency. The researcher took the research location in Bilungala Village, North Bilungala Village, Pelitahijau Village, Tihu Village, Bonepantai District, Bonebolango Regency. With a sample of 43 respondents. This study uses a quantitative approach, with an Ex-post facto research method. The data collection technique was obtained from the results of observation and questionnaire dissemination and used multiple linear regression tests. From the results of the study, it can be concluded that there is a positive and significant influence between transparency and management of village fund allocation in Bilungala, North Bilungala, Pelitahijau by 65%.  While the rest is influenced by other variables that were not studied in this study.